Dead and berried - Cochran, Peg (Cochran, Peg. Cranberry Cove mysteries., 2017)
"It's June in Cranberry Cove and Monica Albertson's plan to sell cranberry relish to chain stores is taking off. The cranberry bogs are in bloom, and local beekeeper Rick Taylor and his assistant Lori Wenk are bringing in bees to pollinate the blossoms. When a fatal prick fells Lori, the buzz is that Rick is to blame. In trying to clear her friend's name, Monica discovers that more than a few people in Cranberry Cove have felt the power of Lori's venom, and it looks as if this time she may have agitated the hive a bit too much. With the fate of the farm on the line, Monica must get to the bottom of the crime before another victim gets stung."--Page 4 of cover.